PROFIL PETANI DALAM MEMANFAATKAN PEKARANGAN DI DESA OTAM (INDUK) KECAMATAN PASSI BARAT KABUPATEN BOLAANG MONGONDOW - Ma’dika .; Martha Mareyke Sendow; Jean Fanny Junita Timban (Sam Ratulangi University, 2020)
This study aims to look at the profile of farmers in utilizing the yard in Otam (Induk) Village, Passi Barat District, Bolaang Mongondow Regency. This research was conducted from September to November 2019. The method of selecting samples was done purposively, namely to farmers who own a plots of land. The data used are primary data and secondary data. Primary data was collected through interviews with 50 respondents, namely farmers owning their plots. Secondary data were obtained from the Otam Village Office. Data analysis in this study uses descriptive analysis in the form of tables and simple calculations. The results showed that the grounds in the village of Otam (Induk) are owned by farmers who mostly have junior high school education. Yard land is used by farmers for various types of plants. Most of the plots are planted Farmers who plant their plots with spice plants for cooking by 40 percent while farmers who plant medicinal plants for treat disease only 16 percent. While farmers who grow vegetables 24%, and those who grow fruits 20% in their yard. Live pharmacy plants, namely: cat's whiskers, bitter, ginger, and ginger. Plants that include a living kitchen in the form of: Galangal, Chinese onions, kulaci (solation), and onion stems. Plants that include vegetables are mustard greens, cabbage, carrots, tomatoes, leilem vegetables and Japanese cucumbers. While the fruit plants include: duku, avocado, langsa, soursop, durian and mango.*eprm*